Translation Specializations within Master of Linguistics Programs in Indonesia: Mapping and Comparing on Curriculum Structure and Epistemological Orientation - Muhamad Saiful Mukminin; Natasya Ayu Salsabilla; Muhammad Habibie Alfath; Aqeel Ahmed; Tareq Alfraidi (Universitas Muhammadiyah Mataram, 2026)
Translation specialization in Indonesian Master of Linguistics programs plays a key role in developing graduates’ theoretical knowledge, practical skills, and research competence. However, variations in curriculum structure, content, and epistemological orientation across universities remain underexplored, necessitating a systematic mapping and comparison study. This study aims to map and compare the curricula of translation specializations in Master of Linguistics programs in Indonesia, including their epistemological orientations. A qualitative approach is used, employing descriptive and comparative methods. The data consist of translation specialization curricula from seven universities, collected from official academic documents such as courses offered, syllabi, and program regulations. Data collection is conducted through a documentation study using purposive sampling. Data analysis involves curriculum mapping, curriculum comparison, and determining epistemological orientation. This study shows that curriculum mapping and comparative analysis of translation specializations within the Master of Linguistics Program in Indonesia reveal common core structures in translation theory, practice, and research methodology. Despite these shared foundations, programs display institutional variations in focus, learning opportunities, and curricular structure. The analysis highlights a dominant hybrid epistemological orientation, combining linguistic theory, Translation Studies, and professional practice. This integrated approach allows students to develop theoretical understanding, practical translation skills, and research competence simultaneously. It is reflecting each program’s academic identity while balancing scholarly rigor with applied and industry-relevant training. The study’s findings inform curriculum development, helping universities balance theory, practice, and research to enhance translation education and align it with academic and professional standards.